The Nanotechnology Applications in Developing Food Products - Jabbar, Mohammed Saad Naif Abdul; Hamza, Adyan Wael Mohamed Abdel; Abbas, Tuqa Abdul Karim Musa (American Journal of Botany and Bioengineering, 2024)
Magical spell has the ability to turn everything touched into gold, in real time scenario one such spell is “Nanotechnology” which has the mystical power to revolutionize every field touched by it. Nanotechnology is now invading the food industry and establishing great potential. Nanotechnology applications in food industry include: encapsulation and delivery of substances in targeted sites, increasing the flavor, introducing antibacterial nanoparticles into food, enhancement of shelf life, sensing contamination, improved food storage, tracking, tracing and brand protection. Nano food processing and products can change the color, flavor, or sensory characteristics; they also change the nutritional functionality, removes chemicals or pathogens from food. Nano food packaging materials may extend food life due to high barrier packaging, improve food safety, alert consumers that food is contaminated or spoiled, repair tears in packaging, and even release preservatives to extend the life of the food in the package. Nanobarcodes are used for safety labeling and monitor distribution of food products. Nanosupplements can be easily incorporated by encapsulation techniques for nutritional and drug delivery systems effectively. The health plays a major role in food the disadvantages of the technology is to be concerned. In particular, gold nanoparticles of curcumin were highlighted. To overcome the poor aqueous solubility and bioavailability of curcumin, emphasize its functional features, and broaden its applications in the food and pharmaceutical industries, many nanoscale systems have been widely applied for its encapsulation and delivery. Over many decades, chitosan as a natural biopolymer has been extensively studied due to its polycationic nature, biodegradability, biocompatibility, non- toxicity, and non – allergenic.